THE IMPACT OF DIGITAL TOOLS ON METACOGNITIVE STRATEGY DEVELOPMENT IN ENGLISH LANGUAGE LEARNERS (International Conference on Modern Science and Scientific Studies, 2025)
This literature review explores the role of digital tools in fostering metacognitive strategy development among English language learners (ELLs). By synthesizing existing research, the paper examines how digital interactive activities—such as gamified apps, AI-driven platforms, and adaptive learning systems—enhance learners' metacognitive awareness, self-regulation, and language proficiency. The analysis reveals key trends, including the effectiveness of reflection prompts, real-time feedback mechanisms, and immersive technologies in promoting metacognitive growth. Additionally, the review identifies gaps in current studies and proposes future research directions for integrating digital metacognitive training into English Language Teaching (ELT) pedagogy.